Development of concept-based video tutorial learning media for basic clothing patternmaking skills - Zulbaidah Zulbaidah; Anni Faridah; Weni Nelmira; Resmi Darni (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aimed to develop and evaluate a concept-based video tutorial for teaching basic clothing patternmaking in the Fashion Design program at SMK Negeri 6 Padang. Using a Research and Development approach with the 4D model Define, Design, Develop, and Disseminate the media was created based on identified student learning difficulties and curriculum needs. The developed video was validated by experts in material, media, and instructional design, yielding high validity scores of 90.5%, 89.7%, and 92.3%, respectively, with an average of 90.8% categorized as highly valid. Field testing was conducted with 30 tenth-grade students using pretests, posttests, and response questionnaires. The results showed a significant increase in learning outcomes, with the average score rising from 62.80 to 83.40 and an N-Gain of 0.55. Student responses were very positive, achieving an overall practicality rating of 88.6%. These findings demonstrate that the video tutorial is valid, practical, and effective for vocational learning.